Simulação do colapso progressivo da seção mestra de um navio militar devido à flexão longitudinal - Oliveira, Jeferson Ferreira de (2017)
The necessity of safeguarding the rights and exercising Brazil's obligations at sea, on the continental shelf and its extension (Blue Amazon), generates the need to design and obtain efficient and reliable combat platforms, which are described in the National Defense Strategy (NDS). Aiming at structural efficiency, this work analyzed the progressive collapse of the midship of a military vessel due to longitudinal bending designed by standard. After the validation of the boundary conditions and the analysis of the midship section, we obtained the percentage differences between the last moments, sagging and hogging, calculated by the norm and those resulting from the simulation by finite elements. The percentage differences between the last buckling stress of the different stiffness and those obtained in the buckling of the profiles and plates were also obtained. The results were 18% and 23% of differences in sagging and hogging, respectively. The overall average difference between the critical stress encountered and the standard stress was 44%.